2002
DOI: 10.1038/sj.jhh.1001437
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of AT1-receptor blockade in the prevention and reversal of atherosclerosis

Abstract: The renin-angiotensin system may contribute to the development and progression of atherosclerosis both by increasing blood pressure and by direct effects on all phases of the atherogenic process. Genetic determinants of renin-angiotensin system activation, notably the DD genotype of angiotensin converting enzyme (ACE), are associated with an increased risk of cardiovascular events, as is increased plasma renin activity. In addition, angiotensin II has been shown to increase the uptake and oxidation of low dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…2,3,40 Recent evidence also points to the possibility that Ang II (acting through AT1-R) may contribute to the inflammatory responses associated with hypercholesterolemia, a condition known to increase the density of AT1-R on endothelial cells and circulating blood cells. 19,33,34 In the present study, we assessed the potential role of AT1-R in mediating the platelet-endothelial and leukocyte-endothelial cell adhesion elicited in the microvasculature by hypercholesterolemia. Our results indicate that AT1-R engagement contributes to the prothrombogenic and proinflammatory phenotype induced in postcapillary venules by hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,40 Recent evidence also points to the possibility that Ang II (acting through AT1-R) may contribute to the inflammatory responses associated with hypercholesterolemia, a condition known to increase the density of AT1-R on endothelial cells and circulating blood cells. 19,33,34 In the present study, we assessed the potential role of AT1-R in mediating the platelet-endothelial and leukocyte-endothelial cell adhesion elicited in the microvasculature by hypercholesterolemia. Our results indicate that AT1-R engagement contributes to the prothrombogenic and proinflammatory phenotype induced in postcapillary venules by hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…30 -32 Furthermore, AT1-R antagonists blunt the atherogenic responses to elevated cholesterol levels and attenuate hypercholesterolemia-induced endothelial cell dysfunction. 3,33,34 Nonetheless, it remains unclear whether and how the AT1-R contributes to the early microvascular alterations elicited by hypercholesterolemia.…”
mentioning
confidence: 99%
“…Similar results were reported in Watanabe rabbits. 14 The mechanism underlying the decrease in atherosclerosis after AT 1 blockade is unknown. Various groups have reported that angiotensin receptor blockers modulate cellular adhesion molecules in atherosclerosis, 15 decrease macrophage accumulation 16 and chemokine expression, 16 and attenuate LDL oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…61 Although there is limited evidence for the involvement of inflammation-dependent processes in the protective effects of AT 1 receptor antagonists in myocardial infarction 62 and stroke, 63 a more compelling case can be made for the involvement of Ang II and AT 1 receptors in the inflammatory responses associated with hypercholesterolemia and atherosclerosis. 64 Hypercholesterolemia is associated with an increased density of AT 1 receptors on endothelial cells, circulating leukocytes, and platelets. 45,54,55 This response is prevented by statin treatment through a mechanism that is independent of the drugs' lipid-lowering effect.…”
Section: Renin-angiotensin Systemmentioning
confidence: 99%